PKM Penyuluhan Permainan Matematika Bagi Para Guru di SDN Cibitung Kulon 01 Pagi - Chrisnaji Banindra Yudha; Eva Oktaviana; Evi Faujiah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
At SD Negeri Cibitung Kulon 01 Pagi the teacher still plays a role as a learning center so that students are less actively involved during learning. This condition makes mathematics learning less attractive in the eyes of students and as a result students are less enthusiastic during the learning process, so that the purpose of holding community service activities is to increase the understanding and ability of teachers of SDN Cibitung Kulon 01 Pagi about fun mathematics learning, while the method used is education in community in the form of socialization activities to increase participants' knowledge / understanding of how to create fun mathematics learning in class. with puzzle tetris math games. The results of the evaluation on the implementation of this PKM were obtained from the number of participants who attended as many as 15 people, 8 teachers understood the material very well or were in the high category, while 5 teachers understood maeri well and only 2 teachers did not understand the material that had been explained. The results of this evaluation are a benchmark that the PKM goals are achieved. The evaluation that has been given to the teacher is in the form of an essay question as many as 25 questions related to the material that has been delivered. The conclusion that can be obtained from the implementation of this community service program is: this socialization activity can increase teachers' knowledge about how to create fun mathematics learning in the classroom. Furthermore, the implementation of this community service activity program has been running smoothly and as expected, both by members of the extension team and community service program participants.Abstract written in English which contains a brief description of the background and objectives, methods of implementation, results and discussion, conclusions and recommendation for follow-up.